UNSUR ROMANTIS SEBAGAI PEMBENTUK ESTETIKA DALAM NOVEL KAU, AKU, DAN SEPUCUK ANGPAU MERAH KARYA TERE LIYE - Agus Yulianto (Balai Bahasa Kalimantan Barat, 2019)
This research aims to describe the romantic elements that create the nuances of beauty found in the novel Kau, Aku, dan Sepucuk Angpau Merah. The problem of this research is how the romantic elements form create the nuances of beauty found in the novel Kau, Aku, dan Sepucuk Angpau Merah. The research method used is a qualitative descriptive method with literature study techniques. The results of the research prove that the romantic elements in the novel are in two aspects, namely the love aspect and the love expression aspect. The aspects contained in the novel are the romance that occurred between Borno and May. The aspects of expression contained in the novel in the form of rich social status of poor, joy and sorrow, true love, loyalty, and dreams are achieved.